1990
DOI: 10.2527/1990.682317x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and maternal genetic effects due to the introduction of Bos taurus alleles into Brahman cattle in Florida: I. Reproduction and calf survival.

Abstract: Pregnancy rate, calf survival rate to weaning and calf age at weaning of several types of crossbred cows (2/3 or more Brahman) were compared to those of straightbred Brahman and Angus cows over a 12-yr period at Subtropical Agricultural Research Station near Brooksville, FL. The purpose of this study was to determine the relative importance of additive vs nonadditive genetic effects on reproductive and calf survival traits in a population of cattle whose foundation was selected on the basis of superior reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 8 publications
3
6
1
1
Order By: Relevance
“…Some of the high costs of producing purebreds are associated with poor calf survivability of straightbred Brahman calves (Cartwright, 1980); mating high percentage Brahman cows to straightbred Brahman bulls may be an effective way to avoid the problems associated with straightbred calf mortality and still produce high-percentage Brahman females for use in F 1 production. The non-Brahman fraction of the crossbred cattle in this project was British (Olson et al, 1990); it may be more attractive for Brahman seedstock producers to use other Bos indicus breeds if preweaning mortality and vigor performance results are similar to those of the present study. Our own unpublished data on Nellore-Brahman cross calves suggests (at best) that calf survival to weaning (but not vigor at birth) may be improved over that of straight Brahman, but the limited number of records prevents anything more than consideration of the notion.…”
Section: Brahman Inheritance Effectssupporting
confidence: 67%
See 1 more Smart Citation
“…Some of the high costs of producing purebreds are associated with poor calf survivability of straightbred Brahman calves (Cartwright, 1980); mating high percentage Brahman cows to straightbred Brahman bulls may be an effective way to avoid the problems associated with straightbred calf mortality and still produce high-percentage Brahman females for use in F 1 production. The non-Brahman fraction of the crossbred cattle in this project was British (Olson et al, 1990); it may be more attractive for Brahman seedstock producers to use other Bos indicus breeds if preweaning mortality and vigor performance results are similar to those of the present study. Our own unpublished data on Nellore-Brahman cross calves suggests (at best) that calf survival to weaning (but not vigor at birth) may be improved over that of straight Brahman, but the limited number of records prevents anything more than consideration of the notion.…”
Section: Brahman Inheritance Effectssupporting
confidence: 67%
“…These cows and their ⁵⁄₆ Brahman daughters were bred either inter se or to Brahman bulls until 1981, when most were culled and removed from the herd. The crossbred calves that these cows produced (n = 936) and contemporary purebred calves (n = 364) were part of the data of Olson et al (1990), who reported calf survival rates. They are included in the present study because the subsequent Brahman herd (even to the present) consisted of high-grade cows that descend from this group in order to augment available pedigree and data.…”
Section: Cattlementioning
confidence: 99%
“…Significant heterosis was detected for cow weight at all times of record (Table 8). The estimate of heterosis for cow weight at weaning was similar in trait units and as a percentage of straightbred means (5.5%) to that reported previously for 6-yr-old cows (Riley et al, 2014) but lower than estimates for Bos indicus-British crosses (e.g., Olson et al, 1990). No heterosis for weight at the estimated time of first conception as heifers was detected for these breeds (Riley et al, 2010).…”
Section: Cow Weights and Changessupporting
confidence: 83%
“…of Brahman-Bos taurus from other studies (0.09 to 0.10; Cartwright et al, 1964;Peacock and Koger, 1980;Prayaga, 2004). The Brahman-Angus estimate was more consistent with the upper range of those estimates but less than the value of 0.25 reported by Olson et al (1990). Brahman-Angus heterosis for calving rate was much larger (0.3) for cows grazing endophyte-infected tall fescue than that for bermudagrass (0.1; Brown et al, 2000).…”
Section: Calving and Weaning Ratementioning
confidence: 50%